PC-based gamma knife radiosurgery dose calculation. - Tseng, Y.J.
The PC-based dose-calculation system designed for gamma knife radiosurgery introduced in this article delivers desired accuracy and is equipped with a friendly graphical user interface to allow foolproof operations. With the ongoing advancement in PC technology, the performance/cost ratio is expected to continue to rise to render more incentive in developing a PC-based dose-calculation system.
Keywords: PC-based dose-calculation system; Computation complexity; Friendly graphical user interface; Gamma knife radiosurgery; Irregularly shaped skull phantom; Isodose distribution; Low-cost system; Performance-cost ratio; Single-shot irradiation; Spherically shaped skull phantom; Three-dimensional volume of interest; Treatment planning; Treatment throughput